Integrative Genomics Implicates Genetic Disruption of Prenatal Neurogenesis in Congenital Hydrocephalus. (16th November 2020) - Panchagnula, Shreyas; Jin, Sheng C; Dong, Weilai; Kundishora, Adam; Moreno-De-Luca, Andres; Furey, Charuta G; Allocco, August A; Walker, Rebecca; Nelson-Williams, Carol; Smith, Hannah; Dunbar, Ashley; Conine, Sierra B; et al.
Abstract: INTRODUCTION: Congenital Hydrocephalus (CH) affects 1/1, 000 live births and costs the US healthcare system over 2 billion annually. Surgical cerebrospinal fluid diversion exhibits high failure rates and substantial morbidity. Limited understanding of pathogenesis warrants identification of crucial genetic drivers underlying CH and their impact on brain development. METHODS: Exome analysis of 381 radiographically-confirmed, neurosurgically-treated sporadic CH probands (including 232 case-parent trios) identified genes with rare de novo or transmitted mutations conferring disease risk. Transcriptome analyses identified mid-gestational brain modules and cell-types enriched for cohort-determined CH risk genes, known genes previously implicated in isolated and syndromic forms of CH, and risk genes of Autism Spectrum Disorder (ASD) and Developmental Disorder (DD). RESULTS: Exome analysis reveals 9 high confidence genes and 55 probable risk genes harboring CH-linked mutations. Together, cohort-determined and known CH genes enrich in a single network ("yellow" module) associated with ASD and DD. Functional profiling of the yellow module yields terms of cell and neuronal differentiation, congenital anomalies of craniofacial development, and behavioral abnormalities. Cohort-determined and known CH genes together enrich in nascent migrating excitatory neurons and cycling mitotic progenitors, occupying earlier stages of differentiation than ASD- and DD-enriched cell-types. CONCLUSION: Genetic drivers of CH converge in a neurodevelopmental network and in early neurogenic cell-types, implicating genetic disruption of early brain development as a primary patho-mechanism for a significant subset of CH patients. Transcriptional overlap with ASD and DD may explain persistence of these conditions in CH patients despite surgical intervention, while greater potency of CH-enriched neural precursors may account for increased frequency of structural brain abnormalities in CH than in ASD or DD alone.